Subnational Oil Resource Governance after the Commodity Boom: The Making and Limitations of Peru’s Closing Development Gaps Plan - Arce, Moises (2024)
To meet the growing global demand for minerals and new energy sources, governments in the Global South advance policy interventions to improve the unequal distribution of the cost and benefits of resource extraction. This paper explains the politics behind the implementation of the Closing Development Gaps (CDG) Plan, a new redistributive plan on behalf of Amazonian Indigenous peoples near the oil circuit in the Loreto region of Peru. It emphasizes the long-lasting impact of mobilizing strategies of indigenous organizations, which relayed critical information to policymakers about the claims both old and new of Indigenous peoples neighboring the oil circuit. It also draws attention to the permeability of state institutions, which allowed newer state agencies with distinct policy streams to advance new solutions to old problems. While the CDG Plan seeks to improve resource governance by focusing on infrastructure gaps (e.g., water and sanitation, electrification), it excludes the “political gaps” and the most contentious claims related to the environment that have moved Amazonian Indigenous peoples into struggle in recent years.